Analisis Faktor-Faktor yang Mempengaruhi Disparitas Indeks Pembangunan Manusia antara Kota Banjarmasin dan Kota Banjarbaru Tahun 2010-2019 - Zakkie, Muhammad; Effendi, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to analyze (1) Utilization of non-timber forest products in Puntik Luar Village, Mandastana District, Barito Kuala Regency (2) Community income from the utilization of products forest non-timber in Village Puntik Luar , District Mandastana , Barito Kuala Regency (3) Comparison of the income of the people who use it. Non-Timber Forest Products with communities that do not utilize Non-Timber Forest Products in Puntik Luar Village, Mandastana District, Barito Kuala Regency Respondents in this study were 52 people, name the community around the forest in Puntik Luar village. This research is quantitative descriptive. Data collection methods used in this study interviews in the kueisoner, observation and documentation. The results that there is an impact use of products forest non-timber income of people Puntik Luar village, the place used in this study is the Puntik village outside the Mandastana sub-district, Barito Kuala district which has an impact on increasing community income, which shows that the community of Puntik Luar village has experienced increased income . The resulting negative impact is the extinction or scarcity of bamboo commodity that is not cultivated by the community around the existing forest. Non-timber forest products used as indicators in this study are the number of non-timber forest products that are used in the form of bamboo and thatch plants.